Characterization of calcium silicate hydrate and calcium hydroxide in nanosilica binder composites - Norsuzailina, Sutan; Ibrahim, Yakub; Kiong, C. S. (Publishing House Nekeri, 2013)
Pozzolanic reaction is the reaction of vitreous silica with calcium hydroxide (C–H), which is formed during the hydration of the ordinary Portland cement (OPC) binder producing additional calcium silicate hydrate (C–S–H) that resembles tobermorite or jennite structure, which is the main constituent for the strength and density in the harden binder paste. The pozzolanic activity includes two parameters; the amount of lime (CaOH) that pozzolan can react with and the rate of reaction. The rate of the pozzolanic activity is related to the surface area of pozzolan particles where higher surface area of pozzolan particle (or finer particle) gives more pozzolanic reactivity [1].